UJI ADAPTASI PADI UNGGUL INPARA-3 DI LAHAN RAWA LEBAK MENGGUNAKAN BERBAGAI PAKET PEMUPUKAN ADAPTIF - Rois Rois; Abd. Syakur; Zainuddin Basri (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
Swamp land is a suboptimal land which is potential for the development of food crops, including rice Inpara varieties. The increase in rice yield planted in suboptimal land, suach as in swamp land is highly determined by a number of factors, including the application of a suitable fertilization package. This experiment was conducted on farmer land via on farm adaptive research (OFAR) approach using Randomized Block Design with 5 fertilization packages. Each fertilization package was repeated 5 times and therefore there were 25 plots used. Each plot was planted with 375 seeds, resulting in a total of 9,375 plants. Fertilization packages tested consisted of: d1 = Farmer's fertilization dosage (50 kg urea/ha + 50 kg phonska/ha); d2 = Fertilization dosage based on soil analysis (116 kg Urea/ha + 81 kg KCl/ha + 88 kg Phonska/ha); d3 = Fertilization dosage based on IRRI interpretation (100 kg Urea/ha + 125 kg Phonska/ha); d4 = Recommended fertilization dosage of BPP (85 kg Urea/ha + 85 kg SP-36/ha + 50 kg KCl/ha); and d5 = Fertilization dosage based on swamp soil test interpretation result (PUTR) (300 kg Urea/ha + 50 kg SP-36/ha + 150 kg KCl/ha). Results of plant height and number of tillers were obtained on the use of d3 and d5 fertilization packages of 100.5 cm and 16.1 tillers respectively. While the average number of panicles, the weight of dried grain per mill and the weight of dry grain per milled per plot was obtained on the use of d5 fertilizer package of 15.7 panicles each, 45.9 grams and 5.0 kg per plot. Keywords : Inpara rice, swamp land, fertilization package